Adapt or preserve: Lecturers’ experiences of teaching and learning during the COVID-19 pandemic in South Africa and their self-directedness - Mahlaba, S. C.; Mentz, E. (South African Journal of Higher Education, 2023)
The COVID-19 pandemic that has engulfed the whole world has given rise to a number of previously disguised challenges to higher educational institutions (HEIs). In the blink of an eye, lecturers had to facilitate learning in remote environments without any prior training. What aroused the interest in this study was the need to know how lecturers at one university dealt with the sudden shift to remote teaching during the pandemic. The way in which lecturers dealt with the shift may reveal their self-directedness. Using a qualitative open-ended questionnaire, we explored lecturers’ experiences of facilitating remote learning during the pandemic with the aim of uncovering their experiences and exploring how these experiences revealed lecturers’ self-directedness. The findings suggest that lecturers had both positive and negative experiences about facilitating online learning in their remote areas. We concluded that, even though lecturers experienced challenges in facilitating remote learning, most of them were able to introduce solutions to those challenges, indicating some element of being self-directed learners.